MRP Winner: ‘I’m never going to have a fairy tale ending:’ Girls’ Perspectives on Disney Films: CCY 4999, Honours Research Project. CD: Kael Reid. - Lam, Joy (Noteworthy: The LA&PS Writing Prizes, 2023)
This compelling Major Research Project showcases the author’s original research and excellent writing. Basing their analysis on the concept that children exercise their own agency when responding to cultural artefacts, the writer uses interviews with three teen girls to explore their status as subjects. In other words, they are not just passive vessels, to be pushed this way and that by cultural rhetoric, but “capable of critically analyzing Disney’s narratives, crafting and exploring new ideas, rationalizing their experiences in connection to their identity and childhood while also proposing new solutions for future generations consuming Disney.” Moreover, the author does well to note how children frequently challenge dominant narratives in ways adults often refuse to acknowledge. To do so would mean caregivers would have to stop thinking of children as objects ready to be moulded and shaped as adults thought best. After an extensive literary review and a well-explained methodology, the authors findings are twofold—first, the subjects were united in their desire for more diverse, complex representations of main characters (both mentally and physically) and second, they each recognized a desperate need to update the Disney genre’s male/female behaviours, and to complicate a dynamic of “one needs help, and one does the helping”. Taken together, this report valuably extends our understanding of children’s audience reception. It’s clear, easy-to-read, and taught the assessors something. It has a level of research and careful analysis of which the author can be justly proud and is a very worthy winner of this Faculty-wide competition.